Nasal adenocarcinoma induced by jaagsiekte sheep retrovirus in a juvenile goat: first report on pathological and molecular findings - Eroksuz, Yesari; Timurkan, Mehmet Ozkan; Berber, Engin; Karabulut, Burak; Kara, Emel; Bostan-Yoru, Hayrunnisa; Eroksuz, Hatice (Springer, 2026)
This study documents the first confirmed case of JSRV-associated nasal adenocarcinoma in a goat through a comprehensive analysis combining histopathological, immunohistochemical, and molecular techniques. An autopsy was conducted on a 12-month-old goat exhibiting progressive nasal obstruction. Tissue samples from the nasal mass were examined histologically using H&E staining. Immunohistochemical (IHC) analysis was performed to detect JSRV capsid protein expression and to assess cellular proliferation markers (Ki-67 and PCNA). Molecular screening via PCR was carried out using primers specific for JSRV, ENTV-1, ENTV-2. The JSRV-positive PCR amplicon was sequenced and subjected to phylogenetic analysis. PCR analysis confirmed the presence of JSRV proviral DNA (385 bp) in the tumor tissue, while results for ENTV-1 and ENTV-2 were negative. Histopathological examination identified a mixed glandular adenocarcinoma arising from the surface and glandular epithelium, with evidence of turbinate bone invasion. IHC revealed multifocal positivity for JSRV capsid antigen and indicated a high proliferation index (30-35%). Phylogenetic analysis classified the detected viral strain within the exogenous JSRV group. The infected goat originated from a herd with no documented contact with sheep. This case provides the first conclusive evidence of JSRV-induced nasal adenocarcinoma in a goat, indicating a potential expansion of the virus's host and tissue tropism. These findings highlight the necessity for further investigation into the viral envelope-receptor interactions and promoter elements that govern JSRV tropism.
Keywords: Jaagsiekte Sheep Retrovirus; Enzootic Nasal Adenocarcinoma; Goat; Pcr; Phylogenetic Analysis; Retroviral Oncogenesis